Histology of the postoperative stomach before and after diversion of bile. Issue 6403 (12th November 1983) - Watt, P C; Sloan, J M; Spencer, A; Kennedy, T L
Abstract : Gastric biopsy specimens were taken in 33 patients before and after procedures to divert bile (construction of Roux loop in 19, closure of gastrojejunostomy in 14). Each biopsy specimen was assessed for dysplasia, intestinal metaplasia, atrophy, and gastritis, each variable being given a score ranging from 0 to 6. Patients were given preoperative and postoperative scores for each of these variables based on the average score of all preoperative or postoperative specimens. Comparison between preoperative and postoperative histology showed that there was no difference for gastritis, atrophy, or intestinal metaplasia. Patients who underwent closure of a gastrojejunostomy showed improvement in dysplasia that was not statistically significant. There was, however, a significant improvement in dysplasia in patients in whom a Roux loop was fashioned (p = 0.006) and in all patients taken together (p = 0.002). It was concluded that procedures that divert bile improve dysplasia but not other histological abnormalities in the stomach postoperatively.